2022
DOI: 10.3390/s22186833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Brazilian Agriculturalists’ IoT Smart Agriculture Adoption Barriers: Understanding Stakeholder Salience Prior to Launching an Innovation

Abstract: The study sought to: (1) evaluate agriculturalists’ characteristics as adopters of IoT smart agriculture technologies, (2) evaluate traits fostering innovation adoption, (3) evaluate the cycle of IoT smart agriculture adoption, and, lastly, (4) discern attributes and barriers of information communication. Researchers utilized a survey design to develop an instrument composed of eight adoption constructs and one personal characteristic construct and distributed it to agriculturalists at an agricultural expositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
(42 reference statements)
3
29
0
Order By: Relevance
“…Another study on a system of rice intensification, an agri-innovation introduced by the government, shows that farmers are reluctant to accept due to incompatible with existing practices while technically complicated [40] . This is also consistent with other recent studies that the simplicity of new agrienvironmental technologies is central to innovation adoption [41,42] .…”
Section: Discussionsupporting
confidence: 92%
“…Another study on a system of rice intensification, an agri-innovation introduced by the government, shows that farmers are reluctant to accept due to incompatible with existing practices while technically complicated [40] . This is also consistent with other recent studies that the simplicity of new agrienvironmental technologies is central to innovation adoption [41,42] .…”
Section: Discussionsupporting
confidence: 92%
“…The number of agrometeorological station networks is increasing, but it is still interesting to have data from the specific location of the crops, which can be obtained by interpolating the data measured by the agrometeorological station network. Strong et al [ 36 ] assessed and evaluated the barriers to the adoption of smart agriculture through the Internet of Things (IoT) among Brazilian farmers in the Rio Grande do Sul, where they found that elements such as compatibility, complexity, testability, and visibility were the predictors of farmers’ adoption of innovative solutions. As for ANN models, they were analyzed in this paper to describe the importance of their application for the adoption of climate-smart agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Elevating agricultural development requires many aspects beyond production (Chaleta et al, 2021). Additional inquiries are needed to understand Extension professionals' use and perceived usefulness of social media professional learning networks (Mikwamba et al, 2021;Strong et al, 2022). Research is necessary to discern the extent learning networks prepare agricultural preservice teachers and offer professional learning for practicing teachers to improve online and social media communications for all digital and face to face learners.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Improving the volume of individuals with access to quality education is a fundamental component of goal 4 (Chankseliani & McCowan, 2021;Huynh et al, 2019). 5G networks have proliferated professional learning networks' availability, which allows users to access the communal knowledge of instructors or researchers across the globe (Strong et al, 2022;Zhou et al, 2022).…”
Section: Introduction and Problem Statementmentioning
confidence: 99%